2021
DOI: 10.2334/josnusd.21-0019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dental esthetic proportions in a Spanish population sample

Abstract: Purpose:The present study aimed to analyze in a Spanish population sample the compliance of the anterior maxillary teeth to the dental esthetic proportions described in the literature. Methods: Photographs of the smiles of 78 individuals were calibrated and digitally analyzed considering the following proportions: golden proportion (GP), recurring esthetic dental (RED), golden percentage (GPG), Preston's proportion and Modified golden percentage (MGPG). For statistical analysis, the t-test of an independent sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
1
14
1
2
Order By: Relevance
“…There have been studies investigating the presence of the P in the natural upper anterior teeth of different populations. The P was not found in studies conducted in England, 45 India 50 and Spain 46 . However, it has been reported that the P, not the RED proportion, can be used in the rehabilitation of anterior maxillary teeth in Portuguese individuals 51 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There have been studies investigating the presence of the P in the natural upper anterior teeth of different populations. The P was not found in studies conducted in England, 45 India 50 and Spain 46 . However, it has been reported that the P, not the RED proportion, can be used in the rehabilitation of anterior maxillary teeth in Portuguese individuals 51 .…”
Section: Discussionmentioning
confidence: 90%
“…43 However, this proportion is not frequently found in the different populations studied. [44][45][46][47][48] No GPR was detected in the anterior teeth of a population of Turks. 48 According to a study conducted in an Indian population, RED was more common in smiles perceived as esthetically pleasing than GPR.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have found the absence of the golden proportion in diferent populations [9,11,12,[16][17][18], as they did not consider the distal portion of the canine in the frontal analysis of the smile. In the invention, canine teeth are analyzed according to their position in the arch and anatomical condition, being divided into a mesial segment and a distal segment.…”
Section: Discussionmentioning
confidence: 99%
“…Este tratamento objetiva recobrir e mascarar defeitos de coloração, reanatomizar elementos dentários, promover fechamento de diastemas e aumentar o tamanho dos dentes, de maneira segura e previsível 9,22 estética, mimetização do esmalte, além de requerer um menor desgaste da estrutura dentária. Tais atributos permitem a realização de tratamentos estético-reabilitadores mais efetivos e conservadores [23][24][25] . Embora ainda desconhecida por muitos, as lentes de contato dentais vêm ganhando espaço na mídia ao despertar o desejo e a curiosidade das pessoas por conhecer e se inteirar mais sobre este, que é um tema comumente discutido nas rodas de conversas, nos programas de televisão, na mídia impressa e no meio acadêmico.…”
Section: Discussionunclassified